Breastfeeding and Maternal Risk of Type 2 Diabetes Mellitus: A Literature Review - Fugas, Agnieszka; Pach, Magdalena; Wierzejska, Natalia; Michalczewska, Aneta; Nowak, Agnieszka; Chmielowiec, Zuzanna; Partyka, Alicja; Dziedzic, Mariola; Smykiewicz, Karolina; Dobrzańska, Justyna (Journal of Education, Health and Sport, 2024)
Breast-feeding offers plenty of benefits for both infants and mothers, however, most studies have mostly been concerned with the health of infants. As far as infants are concerned, breastfeeding is associated with nutritional advantages and a reduced risk of acute otitis media, atopic dermatitis, gastrointestinal infections, lower respiratory tract diseases, asthma, obesity, sudden infant death syndrome or even childhood leukemia. The health outcomes of the breastfeeding mother include reduced risk for breast, endometrial and ovarian cancer are well documented. In our article we will focus on the impact of breast-feeding on lowering the risk of diabetes mellitus in mothers.